Periprocedural outcome in patients undergoing left atrial appendage occlusion with the Watchman FLX device: The ITALIAN-FLX registry - Berti, Sergio; De Caterina, Alberto Ranieri; Grasso, Carmelo; Casu, Gavino; Giacchi, Giuseppe; Pagnotta, Paolo; Maremmani, Michele; Mazzone, Patrizio; Limite, Luca; Tomassini, Francesco; Greco, Francesco; Romeo, Maria Rita; et al. (Frontiers in Cardiovascular Medicine, 2023)
The Watchman FLX is a novel device for transcatheter left atrial appendage occlusion (LAAO) specifically designed to improve procedural performance in more complex anatomies with a better safety profile. Recently, small prospective non-randomized studies have shown good procedural success and safety compared with previous experiences. Results from large multicenter registries are needed to confirm the safety and efficacy of the Watchman FLX device in a real-world setting. Italian FLX registry is a retrospective, non-randomized, multicentric study across 25 investigational centers in Italy including consecutive patients undergoing LAAO with the Watchman FLX between March 2019 and September 2021 (N=772). The primary efficacy outcome was the technical success of the LAAO procedure (peri-device flow ≤ 5 mm) as assessed by intra-procedural imaging. The peri-procedural safety outcome was defined as the occurrence of one of the following events within 7 days after the procedure or by hospital discharge: death, stroke, transient ischemic attack, major extracranial bleeding (BARC type 3 or 5), pericardial effusion with tamponade or device embolization. A total of 772 patients were enrolled. The mean age was 76 ± 8 with a mean CHA2DS2-VASc score of 4.1± 1.4 and a mean HAS-BLED score of 3.7 ± 1.1. Technical success was achieved in 772 (100 %) patients with the first device implanted in 760 (98.4%) patients. A peri-procedural safety outcome event occurred in 21 patients (2.7%) with major extracranial bleeding being the most common (1.7%). No device embolization occurred. At discharge 459 patients (59.4 %) were treated with dual antiplatelet therapy (DAPT). The Italian Flx registry represents the largest multicenter retrospective real-world study reporting periprocedural outcome of LAAO with the Watchman FLX device, resulting in a procedural success rate of 100 % and a low incidence of peri-procedural major adverse events (2.7%).